In vivo efficacy of the boron-pleuromutilin AN11251 against Wolbachia of the rodent filarial nematode Litomosoides sigmodontis. - Alexandra Ehrens; Christopher S Lunde; Robert T Jacobs; Dominique Struever; Marianne Koschel; Stefan J Frohberger; Franziska Lenz; Martina Fendler; Joseph D Turner; Stephen A Ward; Mark J Taylor; Yvonne R Freund; et al. (Public Library of Science (PLoS), 2020)
The elimination of filarial diseases such as onchocerciasis and lymphatic filariasis is hampered by the lack of a macrofilaricidal-adult worm killing-drug. In the present study, we tested the in vivo efficacy of AN11251, a boron-pleuromutilin that targets endosymbiotic Wolbachia bacteria from filarial nematodes and compared its efficacy to doxycycline and rifampicin. Doxycycline and rifampicin were previously shown to deplete Wolbachia endosymbionts leading to a permanent sterilization of the female adult filariae and adult worm death in human clinical studies. Twice-daily oral treatment of Litomosoides sigmodontis-infected mice with 200 mg/kg AN11251 for 10 days achieved a Wolbachia depletion > 99.9% in the adult worms, exceeding the Wolbachia reduction by 10-day treatments with bioequivalent human doses of doxycycline and a similar reduction as high-dose rifampicin (35 mg/kg). Wolbachia reductions of > 99% were also accomplished by 14 days of oral AN11251 at a lower twice-daily dose (50 mg/kg) or once-per-day 200 mg/kg AN11251 treatments. The combinations tested of AN11251 with doxycycline had no clear beneficial impact on Wolbachia depletion, achieving a > 97% Wolbachia reduction with 7 days of treatment. These results indicate that AN11251 is superior to doxycycline and comparable to high-dose rifampicin in the L. sigmodontis mouse model, allowing treatment regimens as short as 10-14 days. Therefore, AN11251 represents a promising pre-clinical candidate that was identified in the L. sigmodontis model, and could be further evaluated and developed as potential clinical candidate for human lymphatic filariasis and onchocerciasis.